2018
DOI: 10.1002/mnfr.201800530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Function of Resveratrol and Genistein as a Regulator of β2‐Adrenergic Receptor Expression in Skeletal Muscle Cells and Characterization of Promoter Elements Required for Promoter Activation

Abstract: The findings show that food-derived molecules have the potential to influence skeletal muscle mass and function by regulating G protein-coupled receptor expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…For example, in the same ob/ob mouse model, we have previously shown that 1) genistein diet has beneficial effects on energy expenditure, T 3 production, and corticosterone status in ob/ob males,17 2) genistein diet has been shown to rescue the number of acetylcholine receptors and decreases the distance between consecutive contractile events in jejunum from female ob/ob mice,16 3) genistein diet improves femur fracture resistance in response to bending loads in ob/ob females 22. Furthermore, literature evidence from others indicates that dietary genistein has a variety of other effects: 1) increases weight of gastrocnemius muscle in mice,23 2) modulates β 2 -adrenergic receptor expression in mouse skeletal muscle,24 3) ameliorates nonalcoholic fatty liver disease,25 4) has protective effects against neuronal degeneration in ApoE mice that fed a high-fat diet (Park et al26), and 5) attenuates intestinal architecture in broiler chicken following lipopolysaccharide-induced deterioration of intestinal morphology 27…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the same ob/ob mouse model, we have previously shown that 1) genistein diet has beneficial effects on energy expenditure, T 3 production, and corticosterone status in ob/ob males,17 2) genistein diet has been shown to rescue the number of acetylcholine receptors and decreases the distance between consecutive contractile events in jejunum from female ob/ob mice,16 3) genistein diet improves femur fracture resistance in response to bending loads in ob/ob females 22. Furthermore, literature evidence from others indicates that dietary genistein has a variety of other effects: 1) increases weight of gastrocnemius muscle in mice,23 2) modulates β 2 -adrenergic receptor expression in mouse skeletal muscle,24 3) ameliorates nonalcoholic fatty liver disease,25 4) has protective effects against neuronal degeneration in ApoE mice that fed a high-fat diet (Park et al26), and 5) attenuates intestinal architecture in broiler chicken following lipopolysaccharide-induced deterioration of intestinal morphology 27…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs have a conserved core of seven transmembrane α-helices that are connected by three extracellular and intracellular loops. Some of these receptors are known as potent inducers of hypertrophy (Berdeaux and Stewart, 2012), and there is evidence about the importance of the regulation of the activation of GPCRs for the maintenance of skeletal muscle function (Chikazawa and Sato, 2018b). They transduce a signal from the extracellular environment to the intracellular ones.…”
Section: Structure and Pathways Related To The β2-adrenergic Receptor's Activationmentioning
confidence: 99%
“…A couple of recent studies by Sato, 2018a, 2018b) showed that it is also possible to increase muscle β2-ar expression by dietary improvement, so this was thought to be a promising strategy for the maintenance of healthy skeletal muscle and for achieving muscle hypertrophy. Resveratrol (a polyphenolic compound) and genistein (an isoflavone found in soybean) were shown to increase the β2-ar mRNA levels in skeletal muscle cells (Chikazawa and Sato, 2018b). Gramine (a natural indole alkaloid) and hordenine (an alkaloid of the phenethylamine class), if administered by intramuscular route, were shown to increase the expression of hypertrophic genes in mice quadriceps, which was suggested to have been mediated, at least in part, by the β2-ar activation, giving new possible therapeutic options (Chikazawa and Sato, 2018a…”
Section: Effect Of β2-adrenergic Receptor's Activation On the Musculoskeletal Systemmentioning
confidence: 99%
See 2 more Smart Citations